The Impact of Literature in English Language Teaching - Challenges and Opportunities: A Literature Review - Satriani, Satriani; Kisman, Kisman; Hamma, Rosmiati; Amaluddin, Amaluddin; Larekeng, Siti Hajar (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The integration of literature into English language teaching (ELT) is increasingly recognized for its ability to enhance linguistic skills and cultural awareness. This literature review aims to provide valuable insights and recommendations for best practices in applying literature within ELT across various educational contexts. Employing a literature review methodology, the study examines both primary and secondary sources, including recent articles, conference papers, and other relevant documents obtained from academic databases and online search engines such as Google Scholar and ERIC. The review process involves selecting pertinent publications, collecting and analyzing data, discussing related topics, integrating supporting information, and drawing conclusions. The findings reveal that while integrating literature into ELT presents certain challenges, such as selecting appropriate texts and addressing varied student proficiency levels, it also offers significant opportunities for enriching language instruction. Additionally, various effective strategies for integrating literature into ELT across different countries are identified. The study highlights the potential of literature to improve English language teaching and provides recommendations for leveraging literary resources to maximize educational benefits.